FEMINISM STUDY OF THE MALE CHARACTER PERSPECTIVE IN THE ORANG KASAR SCRIPT BY ANTON CHEKOV - Syahrotul Latifah; Purwati Anggraini (Jurnal KATA: Penelitian tentang Ilmu Bahasa dan Sastra, 2020)
The purpose of this research is to describe (1) the form of feminism based on the perspective of the main male character; (2) strategies of male main characters in implementing feminism towards female main characters; (3) failure of the perspective of the main male characters in interpreting feminism. This research uses a feminism approach. The method in this research is descriptive analysis method. The source of the research data is the text of Orang Kasar by Anton Chekov. The data in this study are excerpts of dialogue in the text of Orang Kasar by Anton Chekov. The results of the study are as follows (1) the form of feminism based on the perspective of male figures found the thoughts and actions of men who reject the existence of women's character; the necessity of overall equality of mindset, speech, and deeds between men and women; and there are no restrictions on talks between men and women; (2) the strategy of male main characters in carrying out feminism towards female main characters, namely through the thought of male feminism which considers no boundaries in any case with women such as bluffing, arguing, and inviting dueling with women who actually have no mastery about that; (3) Misperception of men in interpreting feminism causes feelings of falling in love with men towards men towards men towards women which causes the perspective of male feminism to no longer be the main thing and accept any error for applying feminism according to male perspective.